An examination of the relationship between hoarding symptoms and hostility. (April 2019) - Mathes, Brittany M.; Kennedy, Grace A.; Cougle, Jesse R.; Schmidt, Norman B.
Abstract: Hoarding disorder (HD) is a persistent and severe psychiatric condition in which individuals are unable to discard possessions, which results in considerable clutter. Individuals who hoard often endorse interpersonal difficulties and social isolation. However, little research has examined mechanisms that may help to explain this relationship. One possible mechanism is hostility, which is characterized by increased sensitivity to real or perceived social threats. The current study examined the relationship between hoarding symptoms and hostility across two undergraduate samples. In study 1, unselected undergraduates ( N = 195) were administered measures of hoarding symptoms, hostile interpretations, and depression and anxiety symptoms. Participants in study 2 ( N = 117) were selected for reporting elevated hoarding symptoms. Study 2 participants were administered the same measures as in study 1, and were additionally randomized to an inclusion or exclusion condition in a social exclusion manipulation. Total hoarding symptoms and hostile interpretations were positively associated across both samples, even when controlling for depression and anxiety. Further, greater hoarding symptoms were associated with increased feelings of hostility in response to social exclusion in study 2. Results suggest that increased sensitivity to social threat may confer risk for hoarding. These findings add to a growing body of research implicating interpersonal factors in the development and maintenance of hoarding disorder.